Antimicrobial resistance in Shiga toxin-producing Escherichia coli other than serotype O157 : H7 in England, 2014–2016. Issue 3 (26th February 2020) - Gentle, Amy; Day, Martin R.; Hopkins, Katie L.; Godbole, Gauri; Jenkins, Claire
Abstract : Introduction. Despite many ongoing surveillance projects and the recent focus on the veterinary and clinical 'One Health' aspects of antimicrobial resistance (AMR), evidence of the extent of any public health risk posed by animal reservoirs with respect to the transmission of resistant strains of Escherichia coli to humans remains varied and contentious. In the UK, the main zoonotic reservoir for the foodborne pathogen Shiga toxin-producing E. coli (STEC) is cattle and sheep. In this study, we adopt an alternative approach to the risk assessment of transmission of AMR E. coli from animals to humans, involving monitoring AMR in isolates of STEC, an established zoonotic, foodborne pathogen, from human cases of gastrointestinal disease. Aim. The aim of this study was to determine the genome-derived AMR profiles for STEC from human cases to assess the risk of transmission of multidrug-resistant STEC from ruminants to humans. Methodology. STEC belonging to 10 different clonal complexes (CCs) ( n =457) isolated from human faecal specimens were sequenced and genome-derived AMR profiles were determined. Phenotypic susceptibility testing was undertaken on all isolates ( n =100) predicted to be resistant to at least one class of antimicrobial. Results. Of the 457 isolates, 332 (72.7 %) lacked identifiable resistance genes and were predicted to be fully susceptible to 11 classes of antimicrobials; 125/332 (27.3 %) carried 1 or more resistance genes, of which 83/125 (66.4 %) were resistant to 3 or more classes of antibiotic. The percentage of isolates harbouring AMR determinants varied between CCs, from 4% in CC25 to 100% in CC504. Forty-six different AMR genes were detected, which conferred resistance to eight different antibiotic classes. Resistance to ampicillin, streptomycin, tetracyclines and sulphonamides was most commonly detected. Four isolates were identified as extended-spectrum β - lactamase producers. An overall concordance of 97.7 % ( n =1075/1100) was demonstrated between the phenotypic and genotypic methods. Conclusion. This analysis provided an indirect assessment of the risk of transmission of AMR gastrointestinal pathogens from animals to humans, and revealed a subset of human isolates of the zoonotic pathogen STEC were resistant to the antimicrobials used in animal husbandry. However, this proportion has not increased over the last three decades, and thismay provide evidence that guidancepromoting responsible practice has been effective.